The Relationship Between Adolescents' Knowledge About Hiv/Aids and Adolescents' Sexual Behavior - Tsamarah Kurniadi; Novria Hesti; Sri Suciana (International Health Sciences Journal, 2026)
Adolescents who lack adequate knowledge about risky sexual behavior are highly likely to engage in such behaviors—such as having multiple sexual partners or unprotected sex. The Indonesia Health Profile 2023 indicates that reported HIV-positive cases have tended to increase over the past eleven years. In 2023 alone, there were 57,299 reported HIV cases and 16,410 AIDS cases. The objective of this study was to examine the association between adolescents’ knowledge of HIV/AIDS and their sexual behavior at Al-Falah Orphanage in Padang.This study employed a quantitative, cross-sectional design. Data were collected at the Al-Falah orphanage in Padang from May to August 2025, involving 40 adolescent participants selected through simple random sampling. Data analysis included univariate and bivariate techniques, using chi-square tests. Among the 40 respondents, 23 (57.5%) had poor knowledge of HIV/AIDS. Additionally, 26 respondents (65.0%) reported engaging in sexual activity. A statistically significant association was found between knowledge of HIV/AIDS and sexual behavior among the adolescents (p = 0.017, < 0.05). The study confirms a significant relationship between adolescents’ knowledge of HIV/AIDS and their sexual behavior at the Al-Falah orphanage in Padang. It is recommended that the orphanage provide educational programs on HIV/AIDS and sexual health. Such programs should address adolescent sexual development, the effects of early sexual activity, and the importance of prevention to help adolescents make informed decisions regarding their sexual health.